Salmonella serotypes and their antimicrobial susceptibility in apparently healthy dogs in Addis Ababa, Ethiopia - Kiflu, Bitsu (BMC Vet Res, 2017)
BACKGROUND: The close bond between pet animals and family members poses risk of infection with zoonotic bacterial pathogens such as Salmonella. No data is available on occurrence of Salmonella in dogs in Ethiopia. The aim of this study was therefore to determine the prevalence, serotype distribution and antimicrobial resistance of Salmonella from feces of apparently healthy dogs in Addis Ababa, Ethiopia. RESULTS: Of the total 360 dogs examined, 42 (11.7%; 95% Confidence limit of 8.5%–15.4%) were positive for Salmonella. Fourteen serotypes were detected and the predominant ones were S. Bronx (n = 7; 16.7%), S. Newport (n = 6; 14.3%), followed by S. Typhimurium, S. Indiana, S. Kentucky, S. Saintpaul and S. Virchow (n = 4; 9.5%) each. Salmonella infection status was significantly associated with history of symptom of diarrhea during the past 60 days (OR = 3.78; CI = 1.76–8.13; p = 0). Highest resistance rates were found for oxytetracycline (59.5%), neomycin (50%), streptomycin (38.1%), cephalothin (33.3%), doxycycline (30.9%), ampicillin (30.9%) and amoxicillin + clavulanic acid (26.2%). Thirty eight (90.5%) of the isolates were resistant or intermediately resistant to at least one of the 16 antimicrobials tested. Resistance to two or more antimicrobials was detected in 30 (71.4%) of the isolates. Resistance to three or more antimicrobials was detected in 19 (45.2%) of the isolates. CONCLUSION: This study demonstrated high carriage rate of Salmonella serotypes known for causing human salmonellosis and large proportion of them were resistant to antimicrobials used in public and veterinary medicine for management of various bacterial infections, suggesting the possible risk of infection of human population in close contact with these dogs by drug resistant pathogens. Therefore, it is vital to work on raising public awareness on zoonotic canine diseases prevention measures and good hygienic practices.